Guardiniho dvojznačný postoj ku Kierkegaardovi pri interpretácii Pascala - Šajda, Peter (Filosoﬁcký časopis)
In the article, I analyze the representation of Blaise Pascal’s thinking that was presented by the German philosopher and theologian Romano Guardini. This author explored Pascal’s philosophy in the 1920s and 1930s when Germany experienced a large wave of interest in Kierkegaard’s thinking, known as the “Kierkegaard Renaissance.” Guardini participated actively in this renaissance but was strongly opposed to using Kierkegaard’s philosophy as an interpretative key for reading Pascal. He was concerned that the fashionable philosophy of Kierkegaard would overshadow Pascal’s intellectual originality. I will try to demonstrate that Guardini did not entirely succeed in resisting the temptation of following popular trends and himself used Kierkegaardian concepts and topics when discussing Pascal’s thought. Thus we encounter in his works a specific image of Pascal that reflects in great measure contemporary intellectual tendencies.